2006
DOI: 10.1200/jco.2006.24.18_suppl.1001
|View full text |Cite
|
Sign up to set email alerts
|

Phase II breast cancer chemoprevention trial of the third generation selective estrogen receptor modulator arzoxifene

Abstract: 1001 Background: Arzoxifene (ARZ) is a third generation SERM with efficacy in metastatic breast cancer but lacking uterine agonist activity. Methods: We conducted a randomized, double-blind, placebo-controlled Phase II prevention trial in 199 high risk women assessing the effects of ARZ 20 mg/day on several risk biomarkers. Biomarkers, including cytomorphology of breast epithelial cells obtained by random periareolar FNA (RPFNA) were assessed at baseline and following 6 months of placebo or ARZ. Subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…More recently, newer selective estrogen receptor modulators (SERMSs) such as arzoxifene, and estrogen synthesis inhibitors such as aromatase inhibitors (letrozole, etc. ), are under evaluation as cancer preventive agents using breast density, cytomorphologic, and other molecular biomarker measurement methods (e.g., insulin-like growth factor (IGF)-1/IGF-BP3 ratio) to assess safety and efficacy [42,97]. However, standard CT methods to determine breast density are not optimal for risk assessment and treatment monitoring in every setting.…”
Section: Breast Cancermentioning
confidence: 99%
“…More recently, newer selective estrogen receptor modulators (SERMSs) such as arzoxifene, and estrogen synthesis inhibitors such as aromatase inhibitors (letrozole, etc. ), are under evaluation as cancer preventive agents using breast density, cytomorphologic, and other molecular biomarker measurement methods (e.g., insulin-like growth factor (IGF)-1/IGF-BP3 ratio) to assess safety and efficacy [42,97]. However, standard CT methods to determine breast density are not optimal for risk assessment and treatment monitoring in every setting.…”
Section: Breast Cancermentioning
confidence: 99%
“… 133 In addition, during other Phase I trials, it was found that arzoxifene caused decreases in proliferating cell nuclear antigen, IGF-1, and IGF binding protein 3. 142 Though no objective response was seen, the hormonal data and results on endometrium prompted Phase II trials. In these trials, results showed that lower doses (20 mg versus 50 mg) of arzoxifene showed better objective response rates, with hormone panels for FSH, LH, and SHBG confirming Phase I results.…”
Section: Benzothiophene Sermsmentioning
confidence: 99%
“…Arzoxifene as a chemopreventive agent was also studied in a phase II trial that randomized 199 women considered at high risk of breast cancer to arzoxifene 20 mg/day versus placebo ( Fabian et al 2006 ; Kimler et al 2006 ). Fifty-two percent of patients were premenopausal, whilst 47% of the postmenopausal women were on hormone replacement therapy (HRT).…”
Section: Outcomes Achieved In Clinical Developmentmentioning
confidence: 99%
“…Fifty-two percent of patients were premenopausal, whilst 47% of the postmenopausal women were on hormone replacement therapy (HRT). At 6 months, arzoxifene improved two risk biomarkers: Mammographic breast density was significantly reduced ( P <0.001), both in terms of the total dense area (+3.8 cm 2 versus −12.9 cm 2 ) and the percent of breast with increased density (+0.8% versus −4.6%) ( Kimler et al 2006 ) IGF-1: IGFBP-3 ratio was significantly reduced ( P =0.001) ( Fabian et al 2006 ). …”
Section: Outcomes Achieved In Clinical Developmentmentioning
confidence: 99%